Short-term clinical outcomes and technical advantages of mini-open endoscope assisted anterior cervical discectomy and fusion in the treatment of cervical spondylotic myelopathy - Zhong, Hua-zhang; Cheng, Li; Wang, Qi-fei; Zhu, Bin; Chen, Lei; Jing, Jue-hua; Tian, Da-sheng; Zhou, Yun (BMC musculoskeletal disorders, 2025)
Although anterior cervical discectomy and fusion (ACDF) is the gold standard for treating cervical spondylotic myelopathy (CSM), it still has several disadvantages in spite the used of microscope. Unilateral biportal endoscopy is a newly developed minimally invasive spine surgery and has many advantages. The study aimed to compare the feasibility, technical advantages and short-term clinical efficacy of mini-open endoscope assisted ACDF (MOEA-ACDF) versus microscopic ACDF and traditional ACDF for the treatment of single-level CSM accompanied by osteophyte formation at the posterior edge of the vertebral body or ossification of posterior longitudinal ligament. Thirty-three patients who treated with MOEA-ACDF (Group A), microscopic ACDF (Group B) and traditional ACDF (Group C) were included. Before surgery, at 1 month after surgery and the last follow-up, imaging indicators (cervical Cobb angle, Cobb angle of fused segment, intervertebral space height of fused segment, intervertebral fusion status), and clinical indicators, including visual analogue scale (VAS) scores for neck and upper extremity pain, Japanese orthopedic association (JOA) score, and neck disability index (NDI) were analyzed. The operations were successfully completed in all groups. The mean follow-up time was 20.5 ± 2.8, 20.2 ± 4.3, and 20.3 ± 3.7 months in Groups A, B, C, respectively. Group A had longer operation time and shorter length of skin incision than Groups B and C (all P < 0.05). All patients in each group had achieved bony fusion during the follow-up period, no significant difference in the time taken for bony fusion was noted between the three groups. Imaging and clinical indicators both improved significantly at 1 month after surgery and the last follow-up compared with before surgery in all groups (all P < 0.05). There was no significant difference in imaging and clinical indicators, JOA recovery rate, and the complication rates among the three group after surgery. For the treatment of CSM accompanied by osteophyte formation at the posterior edge of the vertebral body or OPLL, MOEA-ACDF can achieve satisfactory short-term clinical outcomes, with the advantages of high overall surgical safety, good operation accuracy, less cervical soft tissue damage, low complication rate, and fast postoperative recovery.